Intense, Passionate, Romantic Love: A Natural Addiction? How the Fields That Investigate Romance and Substance Abuse Can Inform Each Other - Fisher, Helen E.; Xu, Xiaomeng; Aron, Arthur; Brown, Lucy L. (Frontiers in Psychology, 2016)
Individuals in the early stage of intense romantic love show many symptoms of substance and non-substance or behavioral addictions, including euphoria, craving, tolerance, emotional and physical dependence, withdrawal and relapse. We have proposed that romantic love is a natural (and often positive) addiction that evolved from mammalian antecedents by four million years ago as a survival mechanism to encourage hominin pair-bonding and reproduction, seen cross-culturally today in Homo sapiens. Brain scanning studies using functional magnetic resonance imaging (fMRI) support this view: feelings of intense romantic love engage regions of the brain’s “reward system,” specifically dopamine-rich regions, including the ventral tegmental area, also activated during drug and/or behavioral addiction. Thus, because the experience of romantic love shares reward pathways with a range of substance and behavioral addictions, it may influence the drug and/or behavioral addiction response. Indeed, a study of overnight abstinent smokers has shown that feelings of intense romantic love attenuate brain activity associated with cigarette cue-reactivity. Could socially rewarding experiences be therapeutic for drug and/or behavioral addictions? We suggest that “self expanding” experiences like romance and expanding one’s knowledge, experience and self-perception, may also affect drug and/or behavioral addiction behaviors. Further, because feelings of romantic love can progress into feelings of calm attachment, and because attachment engages more plastic forebrain regions, there is a rationale for therapies that may help substance and/or behavioral addiction by promoting activation of these forebrain systems through long-term, calm, positive attachments to others, including group therapies. Addiction is considered a negative (harmful) disorder that appears in a population subset; while romantic love is often a positive (as well as negative) state experienced by almost all humans. Thus, researchers have not categorized romantic love as a chemical or behavioral addiction. But by embracing data on romantic love, it’s classification as an evolved, natural, often positive but also powerfully negative addiction, and its neural similarity to many substance and non-substance addictive states, clinicians may develop more effective therapeutic approaches to alleviate a range of the addictions, including heartbreak--an almost universal human experience that can trigger stalking, clinical depression, suicide, homicide and other crimes of passion.